ADAPTASI TANAMAN HORTIKULTURA TERHADAP PERUBAHAN IKLIMPADA LAHAN KERING Adaptation of Horticultural Crops to Climate Change in the Upland - Yusdar Hilman; Suciantini Suciantini; Rini Rosliani (Badan Penelitian dan Pengembangan Pertanian, 2019)
Horticultural products (fruits, vegetables and ornamental crops) which have high competitiveness and added value, require supporting appropriate cultivation technology. The objective of this paper was to sort out adaptive technologies that can be implemented for horticultural cultivation, especially on dry land, to minimize yield loss due to climate changes. Horticultural crops in dry lands faced various problems. Characteristics of horticultural crops, among others were easily damage, bulky, sensitive to water stress and the incidence of pests and diseases. Another issue that has begun to happen in the field is the occurrence of extreme climate change, especially El Nino or La Nina that caused crop failures, damage to agricultural land resources, increased in frequency, extent, and intensity of drought, increased moisture, increased in the susceptibility to pests and the disease. Thus the integrated efforts that are needed in strengthening the capability of dry land to face climate change are by the application of adaptative technology, drafting disaster mitigation concepts, observing climate change, policy analysis related to the application of adaptive technology on climate change. The discussed Horticulture Commodities are focused on economically profitable crops, including: vegetables (potatoes, shallots, chili), fruits (bananas, citrus and melons) and ornamental crops (chrysanthemums, orchids, Polycias and Gerbera) scattered in two zoning zones where namely (i) lowland (0-600 meters above sea level); (ii) highlands (> 600 meters above sea level) and (iii) in both elevations of the site which have wet climates and dry climates. Attempsto be made to promote horticultural crops include performing water-efficient irrigation (drip irrigation), mulching, the use of shading on certain crops, proper fertilization, the use of organic fertilizer, planting system and planting distance, and tolerant varieties. Some adaptative technologies that can be adopted for horticultural crops include (1) developing watersaving irrigation technologies (drip and sprinkler irrigation on shallots), (2) applying healthy crop cultivation (good quality seeds, variety tolerant to disease and sub-optimal environment for tomatoes, red or hot chilli shallots and bananas), (3) using environmentally friendly chemical control (concept of threshold control in red or hot chilli), (4) protecting yield and quality of harvest (the use of silver black mulch on shallots and melons, and the use of shade for ornamental plants on dry land).Keywords: Horticulture, climate change, upland, adaptation technology AbstrakSistem produksi hortikultura (buah buahan, sayuran, dan tanaman hias) yang berdaya saing tinggi dan bernilai tambah memerlukan dukungan teknologi. Tulisan ini merangkum teknologi adaptasi komoditas hortikultura pada lahan kering dalam upaya meminimalisasi tingkat kehilangan hasil akibat perubahan iklim. Usaha tani tanaman hortikultura pada lahan kering dihadapkan pada berbagai masalah, di antaranya tanaman mudah dan cepat rusak, sensitif terhadap cekaman lingkungan, dan rentan terhadap hama dan penyakit. Masalah lain yang berdampak negatif terhadap sistem produksi komoditas hortikultura ialah perubahan iklim ekstrem, terutama el-nino dan la-nina. Perubahan iklim tidak hanya menyebabkan kegagalan panen, tetapi juga merusak sumber daya lahan pertanian, meningkatkan luas areal dan intensitas tanaman yang mengalami kekeringan, meningkatkan kelembaban, dan perkembangan hama dan penyakit tanaman. Oleh karena itu diperlukan integrasi pengelolaan lahan dan aplikasi teknologi adaptif perubahan iklim, penyusunan konsep mitigasi bencana, observasi perubahan iklim, dan analisis kebijakan yang terkait dengan aplikasi teknologi adaptasi terhadap perubahan iklim. Pembahasan difokuskan pada tanaman yang secara ekonomi menguntungkan, antara lain kentang, bawang merah, cabai untuk komoditas sayuran; pisang, jeruk, dan melon untuk komoditas buah-buahan; dan krisan, anggrek, polycias dan gerbera untuk tanaman hias. Komoditas hortikultura tersebut tersebar di dua zonasi ketinggian tempat, yakni dataran rendah (0–600 m dpl) dan dataran tinggi (> 600 m dpl). Beberapa teknologi adaptasi yang dapat diadopsi di antaranya (1) irigasi hemat air (irigasi tetes dan irigasi curah pada bawang merah), (2) budi daya tanaman sehat (benih bermutu, varietas toleran penyakit dan lingkungan suboptimal untuk komoditas kentang, cabai, bawang merah, dan pisang, (3) pengendalian hama dan penyakit ramah lingkungan (konsep ambang pengendalian pada cabai, jeruk), dan (4) perlindungan hasil dan peningkatan kualitas hasil panen (penggunaan mulsa plastik hitam perak pada tanaman bawang merah dan melon, serta penggunaan naungan pada tanaman hias anggrek dan krisan). Kata kunci: hortikultura, perubahan iklim, lahan kering, teknologi adaptasi